Platinum Intercalators of DNA as Anticancer Agents. Issue 12 (20th January 2017) - Pages, Benjamin J.; Garbutcheon‐Singh, K. Benjamin; Aldrich‐Wright, Janice R.
Abstract : The drawbacks of the platinum chemotherapy agents cisplatin, carboplatin and oxaliplatin have inspired the development of compounds with different mechanisms of action. Polyaromatic platinum complexes (PPCs) are a promising anticancer alternative; these bind reversibly with DNA through the insertion of a planar aromatic moiety between nucleobases in a process known as intercalation. PPCs have demonstrated in vitro behaviour remarkably different from that of cisplatin and exhibited cytotoxicity up to one hundred times higher than that of cisplatin in many cell lines. This microreview primarily discusses 1, 10‐phenanthroline‐based complexes of the type [Pt(PL )(AL )] 2+ (where PL is a polyaromatic ligand and AL is an ancillary ligand), including their cytotoxicity, DNA‐binding behaviour and biological activity in vitro and in vivo. Other PPCs within the field, including dual‐mode DNA binders incorporating tethered acridines and other potently cytotoxic complexes, are also covered. Abstract : Polyaromatic platinum complexes (PPCs) capable of intercalating between DNA nucleobases have great chemotherapeutic potential. We provide an overview of PPCs that are known to intercalate with DNA and also exhibit potent activity against cancerous cells and tumours. In particular we focus upon PPCs of phenanthroline and various diamines, which display activity up to 100 times that of cisplatin.